Integrasi Turots dan Nilai-nilai Kebangsaan Indonesia: Studi Pembelajaran Fikih Kebangsaan di Ma’had Aly Pondok Pesantren Lirboyo Kediri - Khoirul Mustamir, Ahmad (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The effort to find a form of scientific integration is a special attraction in this study. However, this study specifically focuses on the integration of turotas and national values ​​in Ma'had Aly Lirboyo, Kediri City. Factually, Ma'had Aly Lirboyo has succeeded in integrating the values ​​recorded in the book Fikih Kebangsaan. In this context, it is important to get answers to the integration logic, integrated values ​​and forms of integration in Ma'had Aly Lirboyo, Kediri City. This study uses interview techniques, comprehensive document studies and participant observation. During the study, research ethics to scientific validation were carried out simultaneously. This is a form of moral accountability for the study. As a result, the values ​​that are confirmed are Indonesian and Islamic values ​​(sourced from turots). All values ​​are formulated in a moderate ideology that is strengthened by the understanding of Ahlusunnah Wal Jamaah. The form of integration is reflected in the learning curriculum which includes courses based on turots books (classics). Implementation of learning in bayani, burhani, and irfani rational thinking to produce graduates who are highly competitive and contribute positively to an increasingly complex global society.